Hydrogen embrittlement behaviour of additively manufactured Inconel 625 alloy - Khor, Ashley Shao Ying (Nanyang Technological University, 2023)
This study investigates the effect of hydrogen diffusion on the microstructure and mechanical properties of additively manufactured Inconel 625. Commercially available Inconel 625 powder feedstock materials were characterized using scanning electron microscopy (SEM) for particle size morphology and distribution. Directed energy deposition (DED) was used to fabricate bulk pieces with different process parameters, with a focus on the laser power and interlayer cooling. The resulting microstructures were analyzed using electron backscatter diffraction (EBSD). Samples were subsequently subjected to electrochemical hydrogen charging, and analyzed using a digital optical microscope. Vickers hardness testing was used to measure mechanical properties before and after hydrogen charging. The study found that the hardness values of the hydrogen charged samples were lower than those of the uncharged samples, indicating embrittlement. The presence of cracks found on the surface of the hydrogen-charged samples provided further evidence of hydrogen diffusion. The study also found that the hardness values of the dilution region were higher than those of the deposition region due to the smaller grain size in the former region. Lastly, addition of an interlayer cooling dwell period was found to increase the hardness value due to grain growth. The study provides insights for optimizing DED process parameters for Inconel 625, with potential implications for improving the mechanical behavior of hydrogen-charged nickel-based alloys.